Electronic Cigarettes in Workplaces: An Emerging Public Health Challenge - Ebrahimi, Mohammad Hossein (Shahroud Journal of Medical Sciences, 2025)
The proliferation of electronic cigarette use in workplace settings presents an emerging public health challenge that demands immediate attention. Although often perceived as a less harmful alternative to conventional tobacco products, growing evidence demonstrates that e-cigarette use in shared work environments poses significant health risks, warranting comprehensive policy intervention.Scientific literature clearly indicates that e-cigarette emissions consist of more than just harmless water vapor. These aerosols contain numerous potentially toxic substances, including nicotine, fine particulate matter, volatile organic compounds, and toxic metals (1). Secondhand exposure to these emissions is particularly concerning in indoor workplaces, where ventilation systems may recirculate contaminants throughout shared air spaces.Recent research has shown that non-users exposed to e-cigarette aerosols exhibit detectable levels of nicotine metabolites and report increased respiratory irritation (2). For vulnerable populations, including employees with pre-existing respiratory conditions such as asthma, this exposure can precipitate adverse health effects and exacerbate underlying conditions (3).Furthermore, the common sight of vaping in the workplace normalizes nicotine use, potentially undermining tobacco control efforts and leading to nicotine initiation among never-users. The presence of vaping devices in work environments also challenges smoking cessation attempts among those trying to quit tobacco products.We advocate for extending existing smoke-free policies to explicitly include electronic cigarettes in all indoor workplaces. This evidence-based approach aligns with recommendations from leading health organizations such as the American Society of Heating, Refrigerating and Air-Conditioning Engineers, which states that e-cigarettes should not be permitted indoors due to their emissions of harmful contaminants (4).Protecting worker health requires proactive measures to ensure indoor air quality remains uncompromised by e-cigarette emissions. Implementing comprehensive vape-free workplace policies represents a necessary step toward safeguarding public health in occupational settings.